Uniportal thoracoscopic extended right apical segmentectomy with virtual-assisted lung mapping: a case report - Masahiro Yanagiya; Ami Wada; Nobuyasu Awano; Takehiro Izumo; Yoshiaki Furuhata (Surgical Case Reports, 2023)
Abstract Background Pulmonary extended segmentectomy is an optional surgical treatment for early-stage non-small cell lung cancer that helps to achieve optimal surgical margins. Here, we describe a challenging instance of extended segmentectomy via uniportal video-assisted thoracic surgery with virtual-assisted lung mapping, a preoperative bronchoscopic dye marking procedure. Case presentation A 72-year-old woman presented with two tumors that were clinically diagnosed as early-stage lung cancer; extended right apical segmentectomy was indicated. Because the tumors had appeared unidentifiable intraoperatively, we performed virtual-assisted lung mapping for tumor localization and delineation of the optimal resection area. Surgery was conducted through a single port. All virtual-assisted lung mapping markings were visible. After dissection of the apical vessels and bronchi, a putative intersegmental line was determined using collateral ventilation. Based on the putative intersegmental plane identified by collateral ventilation and the virtual-assisted lung mapping markings, the resection line was delineated. Extended apical segmentectomy along the resection line was successfully performed via uniportal video-assisted thoracic surgery. The postoperative course was uneventful. The pathological diagnosis was minimally invasive adenocarcinoma and adenocarcinoma in situ. Conclusions Virtual-assisted lung mapping can help to achieve optimal extended segmentectomy via uniportal video-assisted thoracic surgery.